Fruit, seed and pollen morphology of Chorispora DC. species (Brassicaceae) of Turkey - Satil, Fatih; Kaya, Ayla; Ünal, Murat (Bangladesh Journal of Botany, 2018)
Detailed description of fruit, seed and pollen macro- and micromorphological characters of Turkish Chorispora species are provided with illustrations. Typical fruits are linear, straight or strongly curved upward. Nonglandular and glandular trichomes are present or absent. Seeds varied in shape from oblong, oblong-broadly elliptic to subglobose and winged at the apex and base or not. The pollen grains are tricolpate and the basic shape of the pollen grains in species studied is perprolate. The surface sculpturing type is reticulate. Among the studied characters, fruit, seed size and colour, seed shape, fruit trichome structure and pollen size were of taxonomic importance and useful in separating taxa.